The Influence of Need Gratification and Narcissistic Behavior Tendencies on the Intensity of Tiktok Social Media Use among Adolescents During the Covid-19 Pandemic - Fatimah Bin Thaher, Nur; Utari R. Sibua, Rima (International Journal of Social Science, Education, Communication and Economics, 2024)
The problem in this research is raised from the increasing use of social media, especially on the TikTok platform during the Covid-19 pandemic. This research was conducted to determine the increasing intensity of use of social media TikTok, the influence of need gratification and the tendency for narcissistic behavior in teenagers during the Covid-19 pandemic. This research is a type of quantitative research with a survey research method with a psychological scale. Sampling used a nonprobability sampling technique using the incidental method with a sample size of 183 teenage respondents. The research results show that there is an influence of need gratification and tendencies towards narcissistic behavior on the intensity of use of social media TikTok among teenagers during the Covid-19 pandemic.